Impacts of the COVID-19 Pandemic on the Healthcare Provision and Lived Experiences of Patients with Hydrocephalus. (April 2022) - Pricop, Diana F.; Subotic, Arsenije; Anghelescu, Beatrice A.M.; Eagles, Matthew; Hamilton, Mark; Roach, Pamela
The emergence of COVID-19 (SARS-CoV-2) led to distancing measures which acutely affected healthcare infrastructure, leading to limited in-person clinical visits and an increased number of virtual appointments. This study aimed to examine the effects this had on adults with hydrocephalus by describing the lived experiences of a cohort of patients at an outpatient hydrocephalus clinic. Between early May and early July of 2020, remote structured interviews were conducted with participants. Interviews were in-depth and open-ended, allowing participants to reflect and expand on the effects of the social distancing mandate on their well-being and quality of care. Three themes emerged: (1) impacts of changes in treatment provision, (2) impacts of changes in mitigating activities, and (3) impacts of changes on personal well-being. The comprehensive understanding of lived experiences may inform the future provision of healthcare services and social policy. Improved approaches to remote care telemedicine have the potential to facilitate high-quality care.